Faktor-Faktor yang Mempengaruhi Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Namorambe, Deli Serdang: Faktor-Faktor yang Mempengaruhi Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Namorambe, Deli Serdang - Sari Saraswati Purba; Nababan, Agnes Sry Vera (Pena Medika : Jurnal Kesehatan, 2025)
Stunting is a chronic nutritional problem that affects children's physical growth and cognitive development. Deli Serdang Regency is one of the regencies with the highest prevalence, namely 33.8% in 2023. This study aims to analyze the factors that influence the incidence of stunting in toddlers aged 1–5 years in the Namorambe Health Center working area, Deli Serdang. This study used a cross-sectional design, with a sample of 91 respondents randomly selected from a total population of 1,005 toddlers. Data were collected through questionnaires and analyzed using the chi-square test. The results showed that there was a significant relationship between parenting patterns (p = 0.000), maternal knowledge (p = 0.000), and infectious diseases (p = 0.013) with the incidence of stunting. However, there was no significant relationship between family income and the incidence of stunting. The recommendation is that comprehensive interventions are needed, including nutrition education and improving basic health services, to reduce the incidence of stunting